COMMUNITY EMPOWERMENT IN NATURAL RESOURCE MANAGEMENT BASED ON REGIONAL PLANNING IN WALELAGAMA VILLAGE, WESAPUT DISTRICT, JAYAWIJAYA REGENCY - Tambunan, Ayu Anggraini; Difinubun, Muhamad Fagi; Payokwa, Silvia (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
Sustainable management of natural resources in rural areas is a major challenge for many communities in Indonesia, especially in areas that still depend on local natural resources without structured planning. Walelagama Village, Wesaput District, Jayawijaya Regency, is an example of a community that relies heavily on forest management and agricultural land to meet its living needs. However, the lack of integrated regional planning means that natural resource management practices are often unsustainable and have a negative impact on the environment. Therefore, this community service activity aims to increase community capacity in managing natural resources based on regional planning, with a participatory approach that integrates local wisdom and modern technology. The service activity was carried out in September 2024, with participants consisting of 35 people including the village head, village administrators and the local community. The method used in this activity is socialization carried out in the village head's office, followed by group discussions and regional zoning-based planning simulations. In this activity, participants are invited to understand the importance of regional planning to preserve nature while increasing agricultural productivity through appropriate zoning. This simulation allows participants to identify and map conservation, production and settlement areas that suit natural conditions and community needs. The results of this activity show that the people of Walelagama Village are starting to understand the concept of zoning-based regional planning, although there are several challenges that need to be overcome, such as limited technological infrastructure and differences in education levels between participants. Limited access to technology hampers people's ability to utilize data-based planning tools, while differences in education levels affect the level of understanding of the material presented. However, this program succeeded in increasing public awareness of the importance of planned and sustainable natural resource management. Overall, this service program makes a significant contribution in increasing the capacity of the Walelagama Village community in terms of managing natural resources based on regional planning. It is hoped that this activity can be the first step towards implementing better regional planning in the future, which will not only benefit the community, but also support sustainable environmental conservation. In addition, the results of this activity indicate the need for further support in the form of improved technological infrastructure and advanced training programs to ensure the sustainability of natural resource management at the community level.